Aplicación del aprendizaje basado en problemas en el programa de Ingeniería Industrial: caso de estudio aplicado en el curso de Gestión de Cadenas de Suministro - Ruiz-Meza, Jose-Luis; Castellanos-Adarme, Mariel; Alzate-Ortiz, Faber; Flórez-Gutiérrez, Alfredo (Revista Científica, 2021)
Problem-based learning (PBL) is a didactic strategy oriented to the competency-based approach within constructivist theories. PBL generates a collaborative learning process in the student, as well as self-learning and meaningful learning from a contextualized problem situation. This methodology arises to support the process of pedagogical change that occurs under the competency-based approach in higher education in order to generate active learning in students. In this paper, a five-phase methodology was developed (identification of the problem situation, organization of the work for collaborative learning, monitoring and support for self-learning, construction of applied solutions, and evaluations and feedback) to apply PBL in the Supply Chain Management course of the Industrial Engineering Program at Corporación Universitaria del Caribe (CECAR). A systematic literature review was carried out to identify the low application rate of the methodology in the field of industrial engineering. For the application of the strategy, three contextualized problems were taken as a basis, which are associated with companies of the economic sectors that have the highest influence in the generation of the Gross Domestic Product (GDP) of the region. The academic impact on a total of four groups was evaluated. Additionally, the expected competences, performances, and products in the courses were achieved, thus obtaining a great acceptance and efficiency in PBL application.